Identifikasi Daging Ayam Broiler Dengan Pengamatan Struktur Histologis Identification of Broiler Meat With Histological Methods - Filphin Adolfin Amalo (JURNAL KAJIAN VETERINER, 2019)
A study to identification the microscopic structure of broiler meat by histological methods, has been carried out. The meat broiler samples were collected from musculus iliotibialis cranialis has been taken from Kupang supermarket. The tissue samples were fixed, dehydrated and embedded in paraffin and 5 μm sections. Harris-Haematoxilin-Eosin staining method, using to identified of histological structure. Microscopic analysis was performed using a binocular light microscope (100X). The study showed that, histological structure of broiler meat was composed by longitudinally and transverselly skeletal muscle. The nuclei in the periphery of the cell, there are dense connective tissue, fat, with small blood vessels. The skeletal myofibers diameter of muscle is 6,1 ± 0,8 μm. We observed for the presence of endomysium, perimysium and epimysium.